Morphological wing templates of drone bees for populations of Apis mellifera in Ukraine - Cherevatov, V. F.; Galatiuk, O. Y.; Zastulka, M. V.; Behas, V. L.; Kerek, S. S.; Papp, V. V.; Babenko, V. V.; Yarovets, V. I. (Regulatory Mechanisms in Biosystems, 2026)
The testing of morphometric templates (standards) for drone wings, obtained from previous studies of bees in Lviv, Zhytomyr, Kyiv, Sumy, Kharkiv, and Poltava regions of Ukraine, was conducted to assess their suit a bility for determining the subspecies and population affiliation of colonies from local honey bee populations. For this purpose, 1 , 492 drone wings from 14 colonies of a breeding apiary in the Khmelnytskyi region were classified into four clusters based on eight indices: Ci, Dbi, Pci, Disc. sh., Ri (traditional), and Ci.3, Ci.2.1, Ci.2.2 (proposed by the authors). Cluster identification was carried out using morphometric templates: "Car nica", representing a local population of the subspecies A. m. carnica ; "UkrBee" – Ukrainian bees; "UkrStep" – Ukrainian steppe bees (for which subspecies identification has not been reliably established); and "HybrCaucas" – a probable hybrid of the subspecies A. m. caucasica , based on Mahalanobis distances between the centroids of templates and clusters. It was established that four populations of honey bees predominate at the location of the apiary. At the next stage of the study, a classification of 1 , 939 drone wings into two clusters was performed for each of the 22 colonies (an additional 8 colonies were included for further analysis). The identification of phenotypes for each of the clusters was carried out in a similar manner by comparison with the aforementioned templates. This made it possible to identify the subspecies and population affiliation of wing phenotypes for 28 (65%) clusters. The results of identifying subspecies and population affiliation of drone wing phenotypes using templates derived within the framework of classical morphometrics indicate the effectiveness of the applied methodology and can be used for the preliminary assessment of the probable genomic compos i tion of drones and queens in the part related to wing morphology. In addition to its primary objective, this study expands knowledge about the racial composition of honey bees in Ukraine. The obtained information on the probable genomic composition of queens can be applied in breeding programs to increase the presence of desired populations at a given apiary and to eliminate populations or hybrids whose presence is undesirable.